High-resolution sea-level fluctuations during the Mid-Holocene in the Ningshao Coastal Plain region, eastern China - Ling, Chaohao; Xue, Bin; Yao, Shuchun; Zhang, Wenchao; Pan, Dadong; Tang, Lingyu (Frontiers in Ecology and Evolution, 2023)
Sea level changes during the Mid-Holocene directly influenced the Neolithic culture in the Yangtze River Delta region (YRD). However, the high-resolution sea level change characteristics for this period remain unclear. In this study, we performed a high-resolution palynological analysis, including pollen, Dinoflagellate cysts , and Foraminiferal linings, using a high-resolution sediment core from Shanglin Lake, in the North of Ningshao Plain (the south of Hangzhou Bay). 11 accelerator mass spectrometry 14 C(AMS) datings indicate the age of the sediments range from 8 cal ka B.P. to 5.6 cal ka B.P. The results show that during the Mid-Holocene, Shanglin Lake evolved from an estuary -subtidal lagoon -semi-enclosed bay -semi-enclosed lagoon -semi-enclosed bay -enclosed lagoon to a modern freshwater lake. There was a period of no, or minimal, eustatic sea-level rise between 7733 and 7585 cal yr B.P. The Mid-Holocene high sea level comes in 7253-7082 cal yr BP. Between 7000 cal yr BP and 5502 cal yr BP, the sea level is close to modern value. The sea level change during this period had a significant impact on the local Neolithic human activity.